2014
DOI: 10.1080/1331677x.2014.952114
|View full text |Cite
|
Sign up to set email alerts
|

Bank net interest margin related to risk, ownership and size: an exploratory study of the Serbian banking industry

Abstract: The article empirically explores bank-specific, industry-specific and macroeconomic determinants of the net interest margin (NIM) in the Serbian banking industry. The baseline regression results suggest that banks with an above-average equity-to-asset ratio tend to report higher NIMs. The chosen proxy for loan default risk also appears statistically significant, but contrary to what is suggested by theory, indicates that the relation between default risk and the NIM is inverse. Amongst industry-specific determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 36 publications
2
11
2
1
Order By: Relevance
“…For this reason, liquidity of the banking sector was significantly above the prescribed limits. This conclusion is in line with the proof of the authors Marinković & Radović (2014) which concluded that Serbian banks with an above-average equity-to-asset ratio tend to report higher net interest margin, because of "risk aversion". This loan structure contributed to banking sector stability, and indirectly led to a general fall in profitability given a minimum rate of return on investment.…”
Section: Resultssupporting
confidence: 90%
“…For this reason, liquidity of the banking sector was significantly above the prescribed limits. This conclusion is in line with the proof of the authors Marinković & Radović (2014) which concluded that Serbian banks with an above-average equity-to-asset ratio tend to report higher net interest margin, because of "risk aversion". This loan structure contributed to banking sector stability, and indirectly led to a general fall in profitability given a minimum rate of return on investment.…”
Section: Resultssupporting
confidence: 90%
“…The banking sector is particularly important in economies where banks play a central role in the financial system. Furthermore, during a financial crisis, turbulence can lead to a credit crunch, as noted by Marinković and Radović (2014). This can affect banks' activity and spread to other sectors.…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with Poghosyan (2012) that banks are expected to require higher interest margins to compensate for funding riskier projects, and to maintain adequate loan reserves. Marinković and Radović (2014) note 'at least for existing loan customers, if possible, banks will re-price existing loans as they become due or when they are renegotiated. This will generate a positive relation between default risk and the NIM, ceteris paribus'.…”
Section: Bank Specific Factors and Aismentioning
confidence: 99%